When you lose a loved one - Allen, Charles L. (Fleming H. Revell Grand RapidsUS, 1959)
Seeks to strengthen and comfort the bereaved in their struggle to understand and accept their loss. Complemented by several poems by inspirational poet, Helen Steiner Rice.